Perancangan Video Iklan Layanan Masyarakat Tentang Bullying - Deona Firsta, Stevany; Anwar, Ahmad Khoirul (Universitas Sahid Surakarta, 2025)
Bullying is a growing social problem, especially among children and adolescents, with serious impacts on the psychological, academic, and even life of victims. A novelty is that the number of bullying cases is still relatively high in schools, despite various prevention efforts. Data from the Indonesian Child Protection Commission (KPAI), UNICEF, and UNESCO show that physical bullying is the most common type of bullying. Existing educational media are still less engaging and less effective in touching the audience's emotions, so that prevention messages are not optimally conveyed. The urgency of this issue lies in the lack of creative campaign tools that can raise public awareness of the dangers of bullying, tools that are both informative and emotional, thereby encouraging students, parents, and the community to take action and prevent bullying. The design aims to create educational media in the form of a public service announcement video that is communicative, engaging, and able to convey bullying prevention messages to the target audience effectively. The method employed quantitative methods, utilizing measurable instruments such as questionnaires, percentage data, and the number of cases. Additionally, it incorporated design methods from StudioAntelope, which encompass the stages of development, pre-production, production, post-production, and distribution. The process included developing ideas and concepts, developing a storyline, storyboarding, shooting, editing, mixing, and rendering, with distribution through social media. The results are a public service announcement video with a realistic cinematic visual style that conveys a powerful, emotionally engaging message. It is expected to serve as an effective educational tool for reducing bullying, fostering empathy, and encouraging community participation in preventing bullying.